Perceived Determinants of Rental Income Tax Compliance in Eldoret Municipality - Kandie, Elijah Kiptoo; Githaiga, Peter Nderitu; Nekesa, Marion (Accounting Analysis Journal, 2025)
Purpose: Taxes are an important source of government revenue across the globe. Hence, this study sought to assess the influence psychological factor comprising of perceived tax fairness, tax knowledge, and enforcement power, trust in government and social norm on rental income tax compliance from a developing region Method: The study was quantitative in nature. Data was collected using structured questionnaires. The sample consisted of 399 tenants who were selected using random sampling method in Eldoret Municipality.The hypotheses were testing using the results of multiple regression. Findings: The empirical results demonstrated that perceived tax system fairness, enforcement power, tax knowledge, trust in government and social norm are significant determinants of rental income tax compliance.  Novelty: While the previous studies have focused on property owner, this study focused on tenants as key parties in residential tax compliance, thus providing new results regarding the influence of socio-psychological factors on rental income tax compliance.